Análisis semiótico de la imposición religiosa en Huasipungo de Jorge Icaza - Machado Guaño, Andrea Salome (2022)
The purpose of the research was to carry out the analysis of the signs of the work "Huasipungo" by Jorge Icaza, based on a semiotic study to obtain the expressions that show religious imposition through Pierce's triad. With this premise, the research on the state that must be investigated is set semiotic analysis of the work "Huasipungo" and the power of religion. Analysis matrices were created with the purpose of incorporating concepts of the triadic basis of Pierce's theory, classifying the signs, and specifying those referred to in his triad; therefore, aspects of the signs were interpreted as representamen, referent and interpretant associated with religious imposition and evangelization in the life of the indigenous people. Pierce's theory allowed identifying the meaning of fragments of the work with its semiotic load and highlighting the strong criticism of the work in the face of a social-historical reality that afflicted Ecuador; This exposes the symbolic value of literature and its power to manifest the cultural symbols of its representations.